Comparison of drug retention of TNF inhibitors, other biologics and JAK inhibitors in RA patients who discontinued JAK inhibitor therapy. (17th May 2022) - Amstad, Andrea; Papagiannoulis, Eleftherios; Scherer, Almut; Rubbert-Roth, Andrea; Finckh, Axel; Mueller, Ruediger; Dudler, Jean; Möller, Burkhard; Villiger, Peter M; Schulz, Martin M P; Kyburz, Diego
Abstract: Objectives: JAK Inhibitors (JAKi) are recommended DMARDs for patients with moderate-to-severe RA who failed first-line therapy with methotrexate. There is a lack of data allowing an evidence-based choice of subsequent DMARD therapy for patients who had discontinued JAKi treatment. We aimed to compare the effectiveness of TNF inhibitor (TNFi) therapy vs JAKi vs other mode of action (OMA) biologic DMARD (bDMARD) in RA patients who were previously treated with a JAKi. Methods: RA patients who discontinued JAKi treatment within the Swiss RA registry SCQM were included for this observational prospective cohort study. The primary outcome was drug retention for either TNFi, OMA bDMARD or JAKi. The hazard ratio for treatment discontinuation was calculated adjusting for potential confounders. A descriptive analysis of the reasons for discontinuation was performed. Results: Four hundred treatment courses of JAKi were included, with a subsequent switch to either JAKi, TNFi or OMA bDMARD. The crude overall drug retention was higher in patients switching to another JAKi as compared with TNFi and comparable to OMA. A significant difference of JAKi vs TNFi persisted after adjusting for potential confounders. Conclusion: In a real-world population of RA patients who discontinued treatment with a JAKi, switching to another JAKi resulted in a higher drug retention than switching to a TNFi. A switch to a second JAKi seems an effective therapeutic option.